Imaging and target screening for novel avenues for psychiatric disorder treatments - Patton, Jedidiah (My University, 2020)
The JNK pathway is linked to both schizophrenia and depression but its impact is still being investigated. Zebrafish larvae at 7 days post-fertilization, were monitored for evoked motility changes after exposure to a variety of drugs marketed for treatment of schizophrenia or depression, JNK inhibitors, or inhibitors and activators of hubs downstream of JNK. For this, we created a behavioral assay consisting of auditory and visual stimuli to generate startle responses. Zebrafish were tracked in 96-well plates from a top-mounted, infrared camera. Findings showed antidepressants reduced overall motility, while psychotics mostly increased motility based on visual stimuli. Some pharmacological regulators of “driver hubs” replicated the effects of antidepressant drugs. The scope and genetic similarity to humans makes behavioral screens in zebrafish an efficient means for collecting pilot data to guide future behavioral studies in mice, for example. Additionally, investigation of the passive CLARITY method for fluorescent imaging of thick-sliced mouse brain was conducted. The process removes lipids from fixed brain, rendering it transparent to reduce diffraction during imaging of thick specimens in 3D, with less mechanical segmentation. The region of interest for this project was the hippocampus, an important region in relation to schizophrenia pathology and the JNK pathway. Cleared tissue was imaged using laser-scanning confocal fluorescence imaging. Optimized CLARITY sections, approximately three millimeters thick, produced clear coronal images of the hippocampus with Tubulin staining. Imaging techniques, like CLARITY, and behavioral testing with hippocampal focus, offers possibilities for understanding how animals utilize JNK and its role in psychiatric disorders.
Keywords: depression, hippocampus, JNK, mice, schizophrenia, confocal, zebrafish